2004
DOI: 10.1109/lpt.2004.824926
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Position-Resolved Mapping of Chromatic Dispersion and Brillouin Shift Along Single-Mode Optical Fibers

Abstract: Abstract-We describe a new method for performing simultaneous position-resolved measurements of chromatic dispersion and Brillouin shift along single-mode optical fibers. The technique provides consistent high-resolution and low-noise results for both quantities. Our measurements indicate a certain correlation between both magnitudes, although the degree of correlation varies for the different manufacturers tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Figure 3 is a sketch of the second experimental setup for mapping the SBS frequency shift. This distributed measurement is based on a recently-developed pump-probe technique called Brillouin optical time domain analysis (BOTDA) [10]. A CW DFB laser source at 1557 nm, similar to that of the previous setup, was split into pump and probe waves.…”
Section: Brillouin Threshold and Spectrum Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 is a sketch of the second experimental setup for mapping the SBS frequency shift. This distributed measurement is based on a recently-developed pump-probe technique called Brillouin optical time domain analysis (BOTDA) [10]. A CW DFB laser source at 1557 nm, similar to that of the previous setup, was split into pump and probe waves.…”
Section: Brillouin Threshold and Spectrum Measurementsmentioning
confidence: 99%
“…By simply varying the frequency of the continuous probe wave relatively to the pump frequency, the Brillouin gain spectrum could then be fully retrieved at any location along the fiber and the Brillouin shift (ν B ) be unambiguously determined as a function of distance. This method offers several advantages such as no laser frequency drift dependence and no need for a tunable laser source [10]. Since the spatial resolution is given by the pulse duration, we performed two experiments with pulse durations of 20ns and 100ns, respectively.…”
Section: Brillouin Threshold and Spectrum Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these simulations we used the experimental power spectrum of the laser with a random spectral phase on each longitudinal mode [10,27]. There are three key reasons to use this "phenomenological" model: first, high-power fiber lasers exhibit fast intensity instabilities on the time scale of the coherence of the source, as shown by autocorrelation measurements in reference [10].…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…We believe that this difference is due to longitudinal fluctuations of the dispersion. Some measurements in standard telecommunication fibers [27] have shown that these variations of dispersion can be extremely important, specially if we consider that the fiber is relatively old and unconventional. To confirm it, we measured the dispersion in two pieces of 100 m at each end of the 6 km fiber with a pulsed laser at 1550 nm by looking at the location of MI side lobes.…”
Section: Numerical Simulationsmentioning
confidence: 99%